2006
DOI: 10.1055/s-2006-931569
|View full text |Cite
|
Sign up to set email alerts
|

Antimalarial Activity of Biflavonoids from Ochna integerrima

Abstract: IntroductionMalaria is the major parasitic infection in many tropical and subtropical regions, leading to more than one million deaths (principally among African children) out of 400 million cases each year [1] and to major consequent impacts on economic productivity and livelihood [2]. The incidence of malaria is now increasing because of the appearance of multi-drug resistant Plasmodium falcipalum, therefore new and more effective antimalarial drugs are urgently required.Ochna integerrima Merr. (Ochnaceae) i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
35
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 9 publications
4
35
0
Order By: Relevance
“…This indicated that the I-Aring had a hydroxy group at C-7, whereas the II-A-ring had hydroxy groups at C-5 and C-7. The 13 C NMR resonances of the biflavanone were in good agreement with those of chamaejasmin (Niwa et al, 1986) and biliquiritigenin (Ichino et al, 2006). The 2D COSY, HSQC and HMBC experiments confirmed the (I-3,II-3)-connection of the two flavanone units.…”
Section: Structure Elucidationsupporting
confidence: 60%
See 1 more Smart Citation
“…This indicated that the I-Aring had a hydroxy group at C-7, whereas the II-A-ring had hydroxy groups at C-5 and C-7. The 13 C NMR resonances of the biflavanone were in good agreement with those of chamaejasmin (Niwa et al, 1986) and biliquiritigenin (Ichino et al, 2006). The 2D COSY, HSQC and HMBC experiments confirmed the (I-3,II-3)-connection of the two flavanone units.…”
Section: Structure Elucidationsupporting
confidence: 60%
“…The compounds comprised seven (I-3,II-3)-biflavonoids, three bi-4-phenyldihydrocoumarins, an isoflavanone and a C-glucosylated flavone. The known compounds were identified as (+)-chamaejasmin (7) (Niwa et al, 1986) which was the major constituent of the crude extract, isochamaejasmin (8) (Niwa et al, 1984(Niwa et al, , 1986, (I-3,II-3)-biliquiritigenin (9) (Ichino et al, 2006), ormocarpin (10) (Nyandat et al, 1990), diphysin (11) (Stermitz et al, 1993), and isovitexin (12) (de Moreira et al, 2000). Except for ormocarpin, this is the first report of these components in the Ormocarpum genus.…”
Section: Structure Elucidationmentioning
confidence: 90%
“…The cytotoxicity of 4 was a little higher than chloroquine (Table 1), and the effect of prenyl substitution on cytotoxicity was not known because the cytotoxicities of the other compounds were not tested. This result postulates that appropriate introduction of prenyl groups into flavonoids, such as the antimalarial biflavanone [3,4], may lead to more useful derivatives for construction of an antimalarial agent.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, new and more effective antimalarial drugs are necessary [2]. It has been reported that biflavanones and flavonol glycosides were found to possess antimalarial activity [3][4][5][6]. However, there is no report on free flavonoid as the active substance.…”
Section: Introductionmentioning
confidence: 99%
“…Acquired resistance leads to a loss of treatment capacity for currently available drugs (Wellems and Plowe, 2001). Previously, antiprotozoal and antimalarial activity for eight biflavonoids has been reported by Weniger et al (2006) and others (Ichino et al, 2006;Azebaze et al, 2007). The heterosporous fern genus Selaginella is a rich source of biflavonoids (Sun et al, 1997;Silva et al, 1995;Lin et al, 2000;Chen et al, 2005).…”
Section: Introductionmentioning
confidence: 99%